2022
DOI: 10.7759/cureus.24816
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Percutaneous Coronary Intervention Outcomes Among Patients With Obstructive Sleep Apnea, Chronic Obstructive Pulmonary Disease Overlap, and Pickwickian Syndrome (Obesity Hypoventilation Syndrome)

Abstract: Background Obstructive sleep apnea (OSA) is often present in coronary artery disease patients and confers a high risk of complications following percutaneous coronary interventions (PCI). The impact of two commonly associated comorbid conditions, chronic obstructive pulmonary disease (COPD) and obesity hypoventilation syndrome (OHS, Pickwickian syndrome) in OSA patients undergoing PCI has never been studied. Methods The National Inpatient Sample (NIS; 2007-2014) was queried usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Patients who require CABG commonly have comorbidities that can increase the risk of surgery, and 2 comorbidities commonly seen in patients who require CABG are COPD and OSA [ 4 ]. Both COPD and OSA are associated with a decreased oxygen saturation, and in OSA-COPD overlap the decrease can be greater than in either condition alone, resulting in increased morbidity and mortality [ 11 , 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who require CABG commonly have comorbidities that can increase the risk of surgery, and 2 comorbidities commonly seen in patients who require CABG are COPD and OSA [ 4 ]. Both COPD and OSA are associated with a decreased oxygen saturation, and in OSA-COPD overlap the decrease can be greater than in either condition alone, resulting in increased morbidity and mortality [ 11 , 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, individuals with COPD who undergo CABG also have increased risks of perioperative complications, including respiratory infections, longer mechanical ventilation, and prolonged hospitalization [ 15 , 16 ]. Recently, a study by Desai et al [ 17 ] examined the influence of OSA-COPD on outcomes following percutaneous coronary intervention (PCI), and demonstrated that patients with OSA-COPD overlap experienced worse outcomes than those with OSA alone. However, no study has yet evaluated the influence of OSA-COPD overlap in the setting of CABG.…”
Section: Introductionmentioning
confidence: 99%